Hybrid nanomaterials with single-site catalysts by spatially controllable immobilization of nickel complexes via photoclick chemistry for alkene epoxidation - Ghosh, Dwaipayan (2018)
Catalyst deactivation is a persistent problem not only for the scientific community but also in industry. Isolated single-site heterogeneous catalysts have shown great promise to overcome these problems. Here, a versatile anchoring strategy for molecular complex immobilization on a broad range of semiconducting or insulating metal oxide (e.g. titanium dioxide, mesoporous silica, cerium oxide, and tungsten oxide) nanoparticles to synthesize isolated single-site catalysts has been studied systematically. An oxidatively stable anchoring group, maleimide, is shown to form covalent linkages with surface hydroxyl functionalities of metal oxide nanoparticles by photoclick chemistry. The nanocomposites have been thoroughly characterized by techniques including UV-visible diffuse reflectance spectroscopy (UV-DRS), high-resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), infrared spectroscopy (IR), and X-ray absorption spectroscopy (XAS). The IR spectroscopic studies confirm the covalent linkages between the maleimide group and surface hydroxyl functionalities of the oxide nanoparticles. The hybrid nanomaterials function as highly efficient catalysts for essentially quantitative oxidations of terminal and internal alkenes, and show molecular catalyst product selectivities even in more eco-friendly solvents. XAS studies verify the robustness of the catalysts after several catalytic cycles. We have applied the photoclick anchoring methodology to precisely control the deposition of a luminescent variant of our catalyst on the metal oxide nanoparticles. Overall, we demonstrate a general approach to use irradiation to anchor molecular complexes on oxide nanoparticles to create recyclable, hybrid, single-site catalysts that function with high selectivity in a broad range of solvents. We have achieved a facile, spatially and temporally controllable photoclick method that can potentially be extended to other ligands, catalysts, functional molecules, and surfaces.